5.66-12.9p-5.59=-12.7p+2.97

Simple and best practice solution for 5.66-12.9p-5.59=-12.7p+2.97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.66-12.9p-5.59=-12.7p+2.97 equation:


Simplifying
5.66 + -12.9p + -5.59 = -12.7p + 2.97

Reorder the terms:
5.66 + -5.59 + -12.9p = -12.7p + 2.97

Combine like terms: 5.66 + -5.59 = 0.07
0.07 + -12.9p = -12.7p + 2.97

Reorder the terms:
0.07 + -12.9p = 2.97 + -12.7p

Solving
0.07 + -12.9p = 2.97 + -12.7p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '12.7p' to each side of the equation.
0.07 + -12.9p + 12.7p = 2.97 + -12.7p + 12.7p

Combine like terms: -12.9p + 12.7p = -0.2p
0.07 + -0.2p = 2.97 + -12.7p + 12.7p

Combine like terms: -12.7p + 12.7p = 0.0
0.07 + -0.2p = 2.97 + 0.0
0.07 + -0.2p = 2.97

Add '-0.07' to each side of the equation.
0.07 + -0.07 + -0.2p = 2.97 + -0.07

Combine like terms: 0.07 + -0.07 = 0.00
0.00 + -0.2p = 2.97 + -0.07
-0.2p = 2.97 + -0.07

Combine like terms: 2.97 + -0.07 = 2.9
-0.2p = 2.9

Divide each side by '-0.2'.
p = -14.5

Simplifying
p = -14.5

See similar equations:

| 7x+8(9x+57)=-18 | | 44/8.75 | | -4/(x^2-4)=0 | | 2x+(x+3)/6=4 | | 1/7(x-10)=7 | | 38.25=4.5(6.4+x) | | 3.2c-18.2c+13.27=-15.7c+10.05 | | 3x^2=x-1 | | 5(2x-8)=1/5(30+60) | | -99.999=-5.6x-7.6 | | 6-10/11x=16 | | 24=10-3x | | -6(-3+7x)=144 | | 7(-14)[3(-7)-5(-4)]= | | 9b-17-13b=-17-11b | | 8.75/44 | | ((e^11x)-1)/x | | p+2/8=3/9 | | 12s-17=-13+15s-10 | | x-3/3=x-4/4 | | 19j-8=3+20j+9 | | x-0.5+20=37 | | 2x+3+x+7=90 | | -3(7+x)+8=-3(x+7) | | 12p^2-7p+1=0 | | -19-8t=-11t-1-3 | | f(x)=x^2-5x+7 | | X-9+2wx=u | | 7.1(-8.5+x)=37.63 | | 5x-7+2x+9=6x+2+x | | x+(-2)=-3 | | 1/4w=8 |

Equations solver categories